Determinants of financing preferences of micro enterprises - Ahmad, Kamilah; Mohamed Zabri, Shafie; Atan, Siti Anisah; Annuar, Aemi Shazwani (JARDCS, 2018)
In the development of business establishments, the financing factor has always been a major consideration that is always put on top of the organisation’s main priorities. This study examines the type of financing preferences of micro enterprises; and to investigate factors influencing their preferences. Based on 164 valid responses, the findings revealed that most respondents prefer internal funding. While the retained profit and owners’ own savings are the main sources of internal fund; bank loan is the major external source of funding among the respondents. Furthermore educational level, loan documentation and procedures, debt commitment; and growth planning are found to have significant link with the financing preference. This paper ought to provide new evidence and inferable source in financing preference.